THE INFLUENCE OF MICROGRAVITY ON THE GROWTH OF GASB CRYSTALS - Soulayman, Soulayman; Regel, Leda. (Latakia University Journal -Basic Sciences Series, 2018)
Bridgman method was applied, for growing a GaSb crystal under Micro-gravity condition (MG), on the cosmic orbital station "Mir" during the cosmic Syrian-Soviet flight. The mentioned experiment was called "Aphamia" and was carried out using furnace "Crystal". The same experiment was simultaneously carried out at laboratory condition in order to compare obtained crystals and to determine the influence of MG on the growth of GaSb crystal. During this experiment the growth of GaSb crystal with a given conductivity under Earth and MG conditions was performed. The crystal structure, impurity distribution and electro-physical properties of GaSb, were investigated. A comparison with available data in literature is also provided. طبقت طريقة بريدجمان لتنمية بلورة GaSb تحت شرط الجاذبية الميكروية (MG) على المحطة المدارية الفضائية "مير" أثناء الرحلة الفضائية السورية - السوفيتية المشتركة. سميت التجربة المذكورة "أفاميا" ونفذت باستخدام الفرن "البلوري". أنجزت نفس التجربة في نفس الوقت في الشروط المخبرية بهدف مقارنة البلورات التي تم الحصول عليها وتم تحديد تأثير الجاذبية الميكروية على نمو البلورة GaSb. أثناء هذه التجربة، تم تنمية البلورة GaSb بناقلية معينة تحت الأرض وبشروط الجاذبية الميكروية. تم اختبار البنية البلورية وتوزع الاشابة والخواص الفيزيائية-الالكترونية للبلورة GaSb. قورنت النتائج التي حصلنا عليها مع المعطيات المتوفرة في المراجع أيضاً.